2022
DOI: 10.1021/acs.analchem.2c02156
|View full text |Cite
|
Sign up to set email alerts
|

PDA–PEI-Copolymerized Nanodots with Tailorable Fluorescence Emission and Quenching Properties for the Sensitive Ratiometric Fluorescence Sensing of miRNA in Serum

Abstract: Dopamine and polyethyleneimine (PEI) copolymerized nanodots (PDA–PEI nanodots) with both fluorescence emission and quenching features were synthesized by a simple one-step reaction at room temperature. By adjusting the dopamine and PEI ratio as well as the chain length of PEI, the fluorescence emission and quenching properties of PDA–PEI nanodots can be controlled well. Under optimal conditions, the nanodots showed strong green fluorescence emission with an absolute quantum yield of 1–2% and a quenching effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…miRNA detection was also successfully performed in fetal bovine serum as a first demonstration of the performances of PDA-PPy NS in real samples. Thanks to its fluorescence and quenching properties, PDA can also be used as a ratiometric probe, as described in the work of Deng et al [82]. They synthesized nanodots (average diameter of 6.7 nm) from the copolymerization of PDA and polyethyleneimine (PEI).…”
Section: Pda-based Fluorescent Probesmentioning
confidence: 99%
“…miRNA detection was also successfully performed in fetal bovine serum as a first demonstration of the performances of PDA-PPy NS in real samples. Thanks to its fluorescence and quenching properties, PDA can also be used as a ratiometric probe, as described in the work of Deng et al [82]. They synthesized nanodots (average diameter of 6.7 nm) from the copolymerization of PDA and polyethyleneimine (PEI).…”
Section: Pda-based Fluorescent Probesmentioning
confidence: 99%
“…After this phenomenon was reported, FL-PDA NPs have been used in bioimaging, 11 antibacterial treatment, 12,13 tumor therapy 14 and biosensor detection. [15][16][17] For example, Kong et al 18 reported a cost-effective glutathione (GSH) sensor using FL-PDA NPs as a fluorescent signal indicator. Dopamine (DA) was rapidly oxidized into quinone derivatives in the presence of MnO 2 nanosheets (MnO 2 NSs) and then self-polymerized into FL-PDA NPs with the maximum emission intensity at 485 nm, while GSH has the ability to reduce MnO 2 NSs to Mn 2+ , thus inhibiting the formation of FL-PDA NPs.…”
Section: Introductionmentioning
confidence: 99%